TERAPI NEBULIZER DENGAN KONTROL NAPAS TERHADAP FREKUENSI NAPAS DAN SATURASI OKSIGEN PASIEN DENGAN COPD - Asni Hasaini; Muhlisoh Muhlisoh; Diana Pefbrianti; Raziansyah Raziansyah (Universitas Muhammadiyah Banjarmasin, 2022)
The Prevalence in Indonesia of Chronic Obstructive Pulmonary Disease (COPD) is 3.7%. Periodic coughing, dyspnea, and sputum production is symptoms caused and shortness of breath is the main complaint when it comes to health services. COPD can cause hypoxemia, an indicator of decreased oxygen saturation that can cause lung function to deteriorate so that the quality of life decreases so that urgent pharmacological and nonpharmacological care is needed. The purpose of this study was to analyze the effectiveness of nebulizer therapy and breath control on breath frequency and oxygen saturation in patients with COPD. This type of quasi-experimental research with Pretest-Posttest, Non-Equivalent Control Group Design. the sample 50 respondents, in the intervention group, added a breath control that is the position CKD and the PLB and in the then control group is a position of a semi fowler and a PLB. The research instrument used observation sheets and data analysis using the paired t-test and the independent t-test. The results show that there is a difference in breath frequency between the intervention group and the control group p=0.038 with an effectiveness value of 47% and there is a difference in oxygen saturation between the intervention group and the control group p=0,000 with an effectiveness value of 87.5%. the nebulizer therapy and breath control can be used as a combination of nursing interventions in the management of spasms in patients with COPD.